Pengaruh Pengaruh Penggunaan Proyek Diorama Terhadap Kemampuan Berpikir Kreatif Siswa Pada Pembelajaran IPAS - Zulfa, Indana (Gerasi Insan Nusantara, 2025)
This research is based on the lack of activeness of students in participating in the learning process due to monotonous learning, therefore students' creative thinking skills are not honed. The increase in creative thinking is greatly influenced by creative and innovative learning methods. In this case, creative thinking can be enhanced with a diorama project. The objectives of this study are: 1) To determine the effect of the use of diorama projects on the creative thinking ability of grade V students in science learning. 2) To find out how much the use of diorama projects affects the creative thinking ability of grade V students in science learning. This study uses a quantitative approach with a quasi-experimental type of research. This research was carried out at MIN 14 Blitar with a class B sample as an experimental group using a diorama project and class C as a control group using conventional learning. Data was collected through pre-test and post-test creative thinking and questionnaire after implementing the diorama project. The results of this study are, 1) There is a significant influence of the use of diorama projects on the creative thinking ability of class V students in science learning with a sig value. 0.002 because there is a strong relationship between independent variables and dependent variables. 2) The magnitude of the influence was obtained as 0.468 because there are other variables that can theoretically affect creative thinking but are not measured in this study such as learning motivation and students' interests.